Single crystal-to-single crystal site-selective postsynthetic metal exchange in a Zn-MOF based on semi-rigid tricarboxylic acid and access to bimetallic MOFs - Bajpai, Alankriti; Chandrasekhar, Pujari; Govardhan, Savitha; Banerjee, Rahul; Moorthy, Jarugu Narasimha (Chemistry-A European Journal, 2015)
The metal ions in a neutral Zn-MOF constructed from tritopic triacid H3L with inherent concave features, rigid core, and peripheral flexibility are found to exist in two distinct SBUs, that is, 0D and 1D. This has allowed site-selective postsynthetic metal exchange (PSME) to be investigated and reactivities of the metal ions in two different environments in coordination polymers to be contrasted for the first time. Site-selective transmetalation of Zn ions in the discrete environment is shown to occur in a single crystal-to-single crystal (SCSC) fashion, with metal ions such as Fe3+, Ru3+, Cu2+, Co2+, etc., whereas those that are part of 1D SBU sustain structural integrity, leading to novel bimetallic MOFs, which are inaccessible by conventional approaches. To the best of our knowledge, site-selective postsynthetic exchange of an intraframework metal ion in a MOF that contains metal ions in discrete as well as polymeric SBUs is heretofore unprecedented.
Keywords: coordination polymers; metal-exchange; metal-organic frameworks; Metathesis; X-ray crystallography